Long-standing temporomandibular joint dislocation: A rare experience - Kapil Malik; Subhas C Debnath; Apurba K Adhyapok; Kriti Hazarika (Wolters Kluwer Medknow Publications, 2017)
Long-standing temporomandibular joint (TMJ) dislocations persist for more than a month are most challenging to treat. The management of such condition varies widely, from closed reduction to complicated surgical procedures. The choice of an appropriate methodology is questionable. At present, there are no standard rules or conventions for the ideal strategy in different circumstances. This paper attempts to present the experience of managing two cases of long-standing TMJ dislocations.